PENGUKURAN TINGKAT PEMAHAMAN PETANI NILAM TERHADAP KEUANGAN USAHA DI KABUPATEN ACEH TAMIANG - Saiful Bahgia; Hasbi (Lembaga Riset dan Inovasi Kreyat Center, 2024)
This study aims to determine the level of understanding of patchouli farmers towards financial literacy, especially business finance. Based on 3 indicators of financial literacy tested, namely, financial knowledge, financial management behavior (financial attitude), and financial attitude (financial behavior), most of the patchouli farmers still do not properly place their financial posts as planned, so they are often tempted by circumstances when using their finances not in accordance with the initial objectives. This type of research is a descriptive quantitative survey study with a sample of 24 respondents. The research sample was determined using the random sampling method. Then, the sample data was analyzed using descriptive statistics, and data tabulation was carried out and presented in the form of graphs and percentages. A small portion (16.6%) of patchouli farmers' level of understanding is heading towards good conditions.